Nilai Pendidikan Moral Dalam Tortor Mangalehen Goar Pada Masyarakat Mandailing Di Kabupaten Labuhan Batu - Asramilasari Panjaitan (Universitas Negeri Medan, 2017)
ASRAMILASARI PANJAITAN, NIM 2123340005 Moral Education Values In Tortor Mangalehen Goar the Community Mandailaing In Labuhan Batu District. Subject: Sendratasik Dance Education Program. Faculty of Language and Art, State University Medan.2016This study discusses the Tortor Mangalehen Goar contained in Mandailing community in Labuhan Batu District aims to determine the structure of the presentation and moral education value contained in Tortor Mangalehen Goar.To discuss the above research purposes, used theories related to the research topic, such as understanding Mangalehen Goar, understanding Tortor and Moral Education Values.When the study are used in discussing the Moral Education Value In Tortor Mangalehen Goar the Community Mandailaing In Labuhan Batu regency for 2 (two) months, namely in June to August 2016. The study site is a hamlet Haloban Padang District of West bar. The population in this study is Mandailing community, traditional leaders, and events Mangalehen Goar. Analysis of the data in this study using descriptive qualitative data collection techniques with literature study, observation, interviews, and documentation.The results showed that, Values Moral Education contained in Tortor Mangalehen Goar is the values contained in the range of motion tortor mangalehen goar are: (a) preferably, (b) desired, (c) be pursued, (d) appreciated and moral education contained at tortor mangalehen goar offender is liable to a neighbor that responsibility to others include: a). Protecting b). helping c). Inspire d). selfless and responsibility towards oneself, among others: a). protected b). Inspired c). Meets d). support.